Preparation method of CoNiFe-based catalyst for hydrogen production by electrolysis of water
By adopting the preparing method of the CONIFE base catalyst, the problem of low response efficiency in electrolyte hydrogen -making technology and scarcity of catalyst resources are solved, and high -efficiency, stable, and economical hydrogen hydrogen hydrogen reactions are realized.
Patent Information
- Application Number
- CN202411507891.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-28
AI Technical Summary
In the existing electrolytic hydrogen production technology, the reaction kinetics of HER and OER are slower and a higher overpotential is required, resulting in a low energy conversion efficiency. At the same time, commonly used Ru, Ir and Pt-based catalysts have problems of scarce resources, high costs and insufficient stability.
Using the preparation method of CoNiFe-based catalyst, Co salt, Ni salt and Fe salt are dissolved in water, mixed evenly and then heated to form a metal organic gel. After calcination and ball milling, a carbon-coated transition metal oxide is formed, which is combined with carbon Black to improve conductivity and reaction efficiency.
The rate and efficiency of electrolyte hydrogen -making reactions are improved, the stability and economy of catalysts is enhanced, and production costs are reduced.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a method for preparing a CoNiFe-based water electrolysis hydrogen production catalyst. Background Art
[0002] Hydrogen (H2) has been considered one of the cleanest and most promising energy carriers due to its high energy density and green and recyclable combustion products, and is also the most promising candidate in the future low-carbon energy system. However, the current production of hydrogen mainly relies on fossil fuels, which leads to excessive resource consumption and greenhouse gas emissions, bringing serious environmental problems. Therefore, in the next few decades, it is imperative to develop clean and renewable alternative energy sources to gradually replace traditional fossil fuels and promote the transformation of the global energy structure, thereby solving current energy and environmental problems and ensuring the sustainable development of society.
[0003] Among the existing green hydrogen production technologies, water electrolysis is the most mature process. This technology produces oxygen and hydrogen by electrolyzing water. The only raw material required is water without pollutants, and the entire process does not produce any carbon-containing byproducts. Oxygen, as the only byproduct, helps mitigate the greenhouse effect. The produced hydrogen can be further converted into electrical energy and injected into the power grid to provide electricity for various power-consuming systems, optimize the energy structure and improve the security of the power grid.
[0004] The process of producing hydrogen by electrolysis of water includes two key reactions: oxygen evolution reaction (OER) at the anode and hydrogen evolution reaction (HER) at the cathode. Due to the slow reaction kinetics of HER and OER, a higher overpotential is required to proceed normally, resulting in low energy conversion efficiency. Therefore, developing efficient and low-cost catalysts to improve reaction efficiency has become a key research direction.
[0005] Currently, although Ru, Ir and Pt-based materials are considered to be the most effective HER and OER electrocatalysts, these materials have limitations such as scarce resources, high cost and insufficient stability. Future research will focus on finding more economical, stable and highly active alternative catalytic materials to promote further development in this field. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a CoNiFe-based water electrolysis hydrogen production catalyst.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: The present invention first provides a method for preparing a CoNiFe-based catalyst, comprising the following steps: (1) Dissolving Co salt, Ni salt and Fe salt in water to prepare a metal salt solution; dissolving trimesic acid, triazole and poly(ethylene glycol)-poly(propylene glycol)-poly(ethylene glycol) in N,N-dimethylformamide (DMF) to prepare a dispersion solution; mixing the metal salt solution and the dispersion solution evenly, heating and stirring in a water bath until a metal organic gel is formed, and filtering, washing, drying and grinding to obtain a precursor powder; (2) calcining the precursor powder in an air atmosphere to obtain a metal oxide powder; mixing the metal oxide powder and carbon black and ball milling to obtain a mixed powder; calcining the mixed powder in a N2 atmosphere to obtain a CoNiFe-based catalyst.
[0010] As a preferred embodiment of the present invention, in step (1), the total molar concentration of metal ions in the metal salt solution is 0.6-0.8 mol / L; the molar percentages of Co salt, Ni salt and Fe salt are 40-47.5%:40-47.5%:5-20%; preferably, the molar percentages of Co salt, Ni salt and Fe salt are 45%:45%:10%.
[0011] As a preferred embodiment of the present invention, the Co salt, the Ni salt and the Fe salt are respectively nitrates or nitrate hydrates thereof.
[0012] As a preferred embodiment of the present invention, the molar ratio of trimesic acid to triazole is 1:6; in the dispersed solution, the molar concentration of trimesic acid is 0.15-0.2 mol / L, and the mass concentration of poly(ethylene glycol)-poly(propylene glycol)-poly(ethylene glycol) is 30-40 g / L.
[0013] As a preferred embodiment of the present invention, the volume ratio of the metal salt solution to the dispersed solution is 3:11.
[0014] As a preferred embodiment of the present invention, the water bath heating in step (1) is performed at a temperature of 90° C. for 4 hours.
[0015] As a preferred embodiment of the present invention, in step (2), the precursor powder is calcined at a temperature of 450° C. in an air atmosphere for a period of 2 h.
[0016] As a preferred embodiment of the present invention, the mass ratio of metal oxide powder to carbon black is 1:0.5-2; preferably 1:1-2, more preferably 1:1.
[0017] As a preferred embodiment of the present invention, the calcination temperature of the mixed powder in N2 atmosphere is 400-1000°C, and the calcination time is 3h; preferably, the calcination temperature is 400-600°C, and more preferably, the calcination temperature is 600°C.
[0018] The present invention further provides a CoNiFe-based catalyst prepared by the above preparation method.
[0019] The present invention also provides an application of the CoNiFe-based catalyst in the electrolysis of water to produce hydrogen. Specifically, the CoNiFe-based catalyst is loaded on the surface of a conductive substrate as a working electrode in a three-electrode system to electrolyze water.
[0020] More specifically, 4 mg of the catalyst was weighed, 0.3 mL of ultrapure water, 0.6 mL of isopropanol, and 0.1 mL of NaFion solution were added, and the mixture was ultrasonically mixed for 30 min to prepare a catalyst suspension, which was then dropped onto a 0.5 cm × 0.5 cm carbon paper and dried to prepare a catalyst suspension with a catalyst loading of 0.48 mg cm -2 working electrode.
[0021] In the three-electrode system, the working electrode is catalyst-loaded carbon paper, the reference electrode is Ag / AgCl electrode, and the counter electrode is platinum mesh; the device uses 1 M KOH as the electrolyte at room temperature and pressure and performs electrochemical water decomposition through an electrochemical workstation.
[0022] Beneficial effects of the present invention:
[0023] The present invention first sintered the precursor in a muffle furnace, which can fully react at a higher temperature, remove impurities, and improve the purity of the metal oxide. Ball milling the metal oxide and carbon black can make the particle size more uniform, increase the contact area with the carbon black, and enhance its conductivity, thereby improving the reaction efficiency and product uniformity in the subsequent tube furnace sintering process. When the precursor treated by the muffle furnace and ball milling is sintered in a tube furnace, the reaction is more complete, the efficiency is higher, and the time and energy required are less.
[0024] The present invention provides a method for preparing a CoNiFe-based catalyst for hydrogen production by water electrolysis, in which Co-based, Ni-based and Fe-based catalysts are combined with carbon black in a controllable manner to form a carbon-coated transition metal oxide, which is successfully applied to hydrogen production by water decomposition, thereby accelerating the reaction rate; at the same time, the catalytic performance of the carbon-coated ternary CoNiFe alloy for hydrogen production by water electrolysis is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them: Figure 1 is the HER activity diagram of the catalyst in Examples 1-4 of the present invention, Figure 2 The OER activity diagram of the catalyst in Examples 1-4 of the present invention is Figure 3 XRD diagrams of Co, Ni, CoNi and CoNiFe prepared in Examples 1-4 of the present invention.
[0026] Figure 4 HER activity diagram of the catalyst in Example 1 and Examples 5-7 of the present invention.
[0027] Figure 5 This is the OER activity diagram of the catalyst in Example 1 and Examples 5-7 of the present invention.
[0028] Figure 6 HER activity diagram of the catalyst in Example 1 and Examples 8-9 of the present invention.
[0029] Figure 7 This is the OER activity diagram of the catalyst in Example 1 and Examples 8-9 of the present invention.
[0030] Figure 8 HER activity diagram of the catalyst in Example 1 and Examples 10-11 of the present invention.
[0031] Fig. 9 This is the OER activity diagram of the catalyst in Example 1 and Examples 10-11 of the present invention.
[0032] Fig.10 HER activity diagram of the catalyst in Example 1 of the present invention and Comparative Examples 1-3.
[0033] Fig.11 It is the OER activity diagram of the catalyst in Example 1 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0036] Evaluation of electrochemical water splitting performance: The test was carried out using an electrochemical workstation (Donghua Analysis, DH7000C).
[0037] In the three-electrode system, the working electrode is catalyst-loaded carbon paper, the reference electrode is Ag / AgCl electrode, and the counter electrode is platinum mesh; the device is tested at room temperature and pressure with 1 M KOH as the electrolyte.
[0038] First, 4 mg of catalyst was weighed, and 0.3 mL of ultrapure water, 0.6 mL of isopropanol, and 0.1 mL of NaFion solution were added. The mixture was ultrasonically mixed for 30 min to prepare a catalyst suspension. The suspension was then dropped onto a 0.5 cm × 0.5 cm carbon paper and air-dried to prepare a catalyst suspension with a loading of 0.48 mg cm -2 working electrode.
[0039] Secondly, the HER and OER performances were tested separately within a suitable potential range by the linear scanning voltammetry (LSV) method; then the CV curves were continuously tested at different scan rates.
[0040] Finally, the impedance of the catalyst was measured based on a current density of 50 mA cm-2 over the macroscopic area of the electrode. -2 and 100 mA cm -2 As an indicator for evaluating the catalytic activity of the catalyst. Example 1
[0041] The preparation of CoNiFe-based water electrolysis hydrogen production catalyst comprises the following steps: (1) Preparation of precursor: The corresponding metal salts ((Co(NO3)2·6H2O: 2.6195 g, Ni(NO3)2·6H2O: 2.6705 g, Fe(NO3)3·9H2O: 0.8203 g)) were dissolved in water (30 g) to prepare a metal salt solution; Trimesic acid (4.2886 g), 1,2,4-triazole (8.3721 g) and poly(ethylene glycol)-poly(propylene glycol)-poly(ethylene glycol) (4 g) were dissolved in N,N-dimethylformamide (DMF) (103.84 g) to prepare a dispersion solution; The two solutions were mixed and stirred for 30 min to ensure uniform mixing; The mixed solution was transferred to a water bath and heated at 90°C with stirring for 4 h. The metal organic gel produced after the reaction was filtered, washed, dried and then ground (particle size was 0.207 nm) to obtain the precursor powder.
[0042] (2) Calcination of the precursor into carbon-coated transition metal oxides by a two-step process: In the first step, 2 g of the precursor was transferred into a muffle furnace, heated to 450 °C at a rate of 5 °C min-1 in an air atmosphere, and calcined for 2 h. In the second step, the obtained oxide and carbon black (Sanhua Mall, Keqin Carbon EC600JD) were mixed in a mass ratio of 1:1 (i.e., 0.1g:0.1g) and ball milled (frequency: 300*10rpm, time 100s, number of times 24 times). Then, the mixture was moved into a tube furnace and heated at 5℃ min under N2 atmosphere. -1 The temperature is raised to 600° C. at a rate of 100° C. and calcined for 3 h to obtain a black solid powder, which is the catalyst for the water electrolysis hydrogen production reaction.
[0043] (3) The above catalyst was prepared into a working electrode for electrochemical water splitting test: For HER, the catalyst drove 100 mA cm in 1 M KOH electrolyte. -2 The overpotential for the current density is 365 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2 The overpotential for the current density is 372 mV. Example 2
[0044] Preparation of Co-based catalysts for hydrogen production by water electrolysis The metal salt solution is: 5.8212 g of Co(NO3)2·6H2O is dissolved in 30 g of water to prepare a Co salt solution. Other operations are the same as in Example 1.
[0045] The Co-based catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 M KOH electrolyte. -2 The overpotential for the current density is 400 mV; for OER, the catalyst drives 50 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 440 mV. Example 3
[0046] Preparation of Ni-based catalysts for hydrogen production by water electrolysis The metal salt solution is prepared by dissolving 5.9345 g of Ni(NO3)2·6H2O in 30 g of water to obtain a Ni salt solution. Other operations are the same as those in Example 1.
[0047] The Ni-based catalyst was prepared as a working electrode for electrochemical water splitting tests: for HER, the catalyst drove 100 mA cm in 1 M KOH electrolyte. -2 The overpotential for the current density is 383 mV; for OER, the catalyst drives 50 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 825 mV. Example 4
[0048] Preparation of CoNi-based catalysts for hydrogen production by water electrolysis The metal salt solution is: Co(NO3)2·6H2O (2.9106 g) and Ni(NO3)2·6H2O (2.9672 g) are dissolved in water (30 g) to prepare a CoNi salt solution; other operations are the same as in Example 1.
[0049] The CoNi-based catalyst was prepared as a working electrode for electrochemical water splitting tests: for HER, the catalyst drove 100 mA cm in 1 M KOH electrolyte. -2 The overpotential for the current density is 419 mV; for OER, the catalyst drives 50 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 470 mV. Example 5
[0050] The difference between this embodiment and embodiment 1 is that the calcination temperature in the second step of step (2) is 400°C.
[0051] The catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 375 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2 The overpotential for the current density is 402 mV. Example 6
[0052] The difference between this embodiment and embodiment 1 is that the calcination temperature in the second step of step (2) is 800°C.
[0053] The catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 394 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2The overpotential for the current density is 415 mV. Example 7
[0054] The difference between this embodiment and embodiment 1 is that the calcination temperature of the second step of step (2) is 1000°C.
[0055] The catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 370 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2 The overpotential of the current density is 471 mV. Example 8
[0056] The difference between this embodiment and embodiment 1 is that the metal salt solution in step (1) is prepared by dissolving the corresponding nitrates (Co(NO3)2·6H2O: 2.7651 g, Ni(NO3)2·6H2O: 2.8189 g, Fe(NO3)3·9H2O: 0.4102 g)) in water (30 g) to obtain a metal salt solution. The other operations are the same as those in embodiment 1.
[0057] The catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 423 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2 The overpotential for the current density is 420 mV. Example 9
[0058] The difference between this embodiment and embodiment 1 is that the metal salt solution in step (1) is prepared by dissolving the corresponding nitrates (Co(NO3)2·6H2O: 2.3285 g, Ni(NO3)2·6H2O: 2.3738 g, Fe(NO3)3·9H2O: 1.6406 g)) in water (30 g) to prepare a metal salt solution. The other operations are the same as those in embodiment 1.
[0059] The catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 402 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2 The overpotential of the current density is 392 mV. Example 10
[0060] The difference between this embodiment and embodiment 1 is that in the second step of step (2), the obtained oxide and carbon black are mixed and ball-milled in a mass ratio of 1:2 (i.e., 0.05 g:0.1 g), and the other steps are the same as those in embodiment 1.
[0061] The catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 400 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2 The overpotential for the current density is 426 mV. Embodiment 11
[0062] The difference between this embodiment and embodiment 1 is that in the second step of step (2), the obtained oxide and carbon black are mixed and ball-milled in a mass ratio of 2:1 (i.e., 0.1 g:0.05 g), and the other steps are the same as those in embodiment 1.
[0063] The catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 376 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2 The overpotential of the current density is 397 mV. Comparative Example 1
[0064] The difference between this comparative example and Example 1 is that the first calcination operation in step (2) is not performed, and 2 g of the precursor powder and carbon black are directly mixed and ball-milled in a mass ratio of 1:1 (i.e., 0.1 g:0.1 g), and the temperature is raised to 600°C at a rate of 5°C min-1 under a N2 atmosphere, and the mixture is kept at this temperature and calcined for 3 h to obtain a catalyst for water electrolysis hydrogen production reaction.
[0065] The catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 395 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2 The overpotential of the current density is 396 mV. Comparative Example 2
[0066] The difference between this comparative example and Example 1 is that carbon black is not added in the second step of step (2), and the other operations are the same as those in Example 1.
[0067] The catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 370 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2 The overpotential for the current density is 380 mV. Comparative Example 3
[0068] The precursor was prepared according to the method of Example 1, and the precursor was moved into a tube furnace and heated at 5°C min under N2 atmosphere. -1 The temperature was raised to 600 °C at a rate of 100 °C and kept warm for calcination for 3 h to obtain a catalyst for water electrolysis to hydrogen production.
[0069] The catalyst was prepared as a working electrode for electrochemical water splitting test: for HER, the catalyst drove 100 mA cm in 1 MKOH electrolyte. -2 The overpotential for the current density is 418 mV; for OER, the catalyst drives 50 mA cm in 1 M KOH electrolyte. -2 The overpotential for the current density is 427 mV.
[0070] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a CoNiFe-based catalyst, characterized in that: The steps include: (1) Dissolving Co salt, Ni salt and Fe salt in water to prepare a metal salt solution; dissolving trimesic acid, triazole and poly(ethylene glycol)-poly(propylene glycol)-poly(ethylene glycol) in N,N-dimethylformamide to prepare a dispersion solution; mixing the metal salt solution and the dispersion solution evenly, heating and stirring in a water bath until a metal organic gel is formed, filtering, washing, drying and then grinding to obtain a precursor powder; (2) calcining the precursor powder in an air atmosphere to obtain a metal oxide powder; mixing the metal oxide powder with carbon black and ball milling to obtain a mixed powder; and calcining the mixed powder in a N2 atmosphere to obtain a CoNiFe-based catalyst.
2. The method for preparing a CoNiFe-based catalyst according to claim 1, characterized in that: The total molar concentration of metal ions in the metal salt solution of step (1) is 0.6-0.8 mol / L; the molar percentages of Co salt, Ni salt and Fe salt are 40-47.5%: 40-47.5%: 5-20%.
3. The method for preparing a CoNiFe-based catalyst according to claim 1, characterized in that: The molar concentration of trimesic acid in the dispersed solution of step (1) is 0.15-0.2 mol / L, the mass concentration of poly(ethylene glycol)-poly(propylene glycol)-poly(ethylene glycol) is 30-40 g / L, the molar ratio of trimesic acid to triazole is 1:6; and / or the volume ratio of the metal salt solution to the dispersed solution is 3:
11.
4. The method for preparing a CoNiFe-based catalyst according to claim 1, characterized in that: The water bath heating temperature in step (1) is 90° C. and the heating time is 4 h.
5. The method for preparing a CoNiFe-based catalyst according to claim 1, characterized in that: In the step (2), the calcination temperature of the precursor powder is 450° C. and the calcination time is 2 h.
6. The method for preparing a CoNiFe-based catalyst according to claim 1, characterized in that: The mass ratio of the metal oxide powder to the carbon black is 1:0.5-2.
7. The method for preparing a CoNiFe-based catalyst according to claim 1, characterized in that: The calcination temperature of the mixed powder is 400-1000°C, and the calcination time is 3h.
8. A CoNiFe-based catalyst prepared by the method according to any one of claims 1 to 7.
9. Use of the CoNiFe-based catalyst according to claim 8 in producing hydrogen by electrolysis of water.
10. The use according to claim 9, characterized in that: The CoNiFe-based catalyst is loaded on the surface of a conductive substrate to prepare a working electrode, and a three-electrode system is constructed to electrolyze water.
Citation Information
Patent Citations
Method for preparing electrocatalytic water-splitting oxygen production electrode
CN105369306A
Modification method of high-voltage lithium nickel manganese oxide positive electrode material
CN115458727A
Preparation method of carbon-coated manganese-doped CoP difunctional water decomposition electrode
CN115786932A
AU2020103244A4